Idiosyncratic Risk and Volatility Bounds, or Can Models with Idiosyncratic Risk Solve the Equity Premium Puzzle? - Lettau, Martin (The Review of Economics and Statistics, 2002)
May 01 2002 Idiosyncratic Risk and Volatility Bounds, or Can Models with Idiosyncratic Risk Solve the Equity Premium Puzzle? Martin Lettau Martin Lettau Federal Reserve Bank of New York and Centre for Economic Policy Research Search for other works by this author on: This Site Google Scholar Author and Article Information Martin Lettau Federal Reserve Bank of New York and Centre for Economic Policy Research Received: April 20 1999 Accepted: May 10 2001 Online Issn: 1530-9142 Print Issn: 0034-6535 © 2002 President and Fellows of Harvard College and the Massachusetts Institute of Technology2002 The Review of Economics and Statistics (2002) 84 (2): 376–380. https://doi.org/10.1162/rest.2002.84.2.376 Article history Received: April 20 1999 Accepted: May 10 2001 Cite Icon Cite Permissions Share Icon Share Facebook Twitter LinkedIn MailTo Views Icon Views Article contents Figures & tables Video Audio Supplementary Data Peer Review Search Site Citation Martin Lettau; Idiosyncratic Risk and Volatility Bounds, or Can Models with Idiosyncratic Risk Solve the Equity Premium Puzzle?. The Review of Economics and Statistics 2002; 84 (2): 376–380. doi: https://doi.org/10.1162/rest.2002.84.2.376 Download citation file: Ris (Zotero) Reference Manager EasyBib Bookends Mendeley Papers EndNote RefWorks BibTex toolbar search Search Dropdown Menu toolbar search search input Search input auto suggest filter your search All ContentAll JournalsThe Review of Economics and Statistics Search Advanced Search This content is only available as a PDF. © 2002 President and Fellows of Harvard College and the Massachusetts Institute of Technology2002 Article PDF first page preview Close Modal You do not currently have access to this content.